Evaluating the surgical and oncological outcomes of hepatic artery variations in minimally invasive pancreaticoduodenectomy: insights from 2023 data at a high-volume pancreatic center - Tianyu Li; Liangbo Dong; Dongming Zhang; Jiashu Han; Menghua Dai; Junchao Guo; Qiang Xu; Weibin Wang; Xianlin Han; Chen Lin (World Journal of Surgical Oncology)
Abstract Background Minimally invasive pancreaticoduodenectomy (MIPD) has seen increased adoption due to advancements in surgical techniques and technology. However, the impact of hepatic artery variations (HAV) and clinically relevant HAV (CR-HAV) on MIPD outcomes remains under-investigated. This study aims to explore the differences in surgical and oncological outcomes of MIPD with or without HAV and CR-HAV. Methods We enrolled 267 consecutive patients who underwent MIPD at Peking Union Medical College Hospital between January and December 2023. HAV was identified preoperatively through enhanced abdominal CT and three-dimensional reconstruction, and classified according to the Michels and Hiatt systems. Clinically relevant hepatic artery variations (CR-HAV) were defined based on their potential impact on the surgical approach. We collected and analyzed perioperative data and oncological outcomes between patients with and without HAV and CR-HAV. Propensity score matching (PSM) was used to minimize baseline confounding. Survival analysis was performed using the Kaplan-Meier method with log-rank tests. Results HAV was identified in 26.1% of patients, and CR-HAV in 18.9%. The median operation time was significantly longer in HAV (+) group compared to HAV (-) group (6.72 vs. 5.80 h, p = 0.013). No significant differences were found between HAV/CR-HAV (+) and (-) groups regarding intraoperative blood loss, conversion to laparotomy, postoperative complications, surgical mortality, length of stay, re-operation, and re-admission. Kaplan-Meier survival analysis showed no significant differences in overall survival or progression-free survival between HAV/CR-HAV (+) and (-) groups in the malignant cohort. Conclusion HAV and CR-HAV do not significantly impact overall or progression-free survival in patients undergoing MIPD. While HAV is associated with longer operation times, other perioperative and oncological outcomes remain comparable between HAV/CR-HAV (+) and (-) groups.